2013
DOI: 10.1103/physreva.88.042707
|View full text |Cite
|
Sign up to set email alerts
|

Ion-impact-induced interatomic Coulombic decay in neon and argon dimers

Abstract: We investigate the contribution of Interatomic Coulombic Decay induced by ion impact in neon and argon dimers (Ne 2 and Ar 2 ) to the production of low energy electrons. Our experiments cover a broad range of perturbation strengths and reaction channels. We use 11.37 MeV/u S 14+ , 0.125 MeV/u He 1+ , 0.1625 MeV/u He 1+ and 0.150 MeV/u He 2+ as projectiles and study ionization, single and double electron transfer to the projectile as well as projectile electron loss processes.The application of a COLTRIMS react… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 65 publications
0
43
0
Order By: Relevance
“…Of particular interest is the resonant ICD (RICD) where the precursor excitation to form an inner-shell vacancy is accomplished by promoting an inner electron to an excited state by an external stimulant, generally electromagnetic radiation [17,18] or, more recently, chargeparticle impact [21]. A theoretical study of RICD followed by Ne 2s → np excitations in MgNe clusters suggested the leading contribution of RICD among other interatomic decay modes [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest is the resonant ICD (RICD) where the precursor excitation to form an inner-shell vacancy is accomplished by promoting an inner electron to an excited state by an external stimulant, generally electromagnetic radiation [17,18] or, more recently, chargeparticle impact [21]. A theoretical study of RICD followed by Ne 2s → np excitations in MgNe clusters suggested the leading contribution of RICD among other interatomic decay modes [22].…”
mentioning
confidence: 99%
“…ICD followed by resonant Auger decay has been identified in Ar dimers using momentum resolved electron-ion-ion coincidence spectroscopy [10,11]. Ultrafast ICDs of a dicationic monomer in a cluster to produce a cluster tricataion [12] Of particular interest is the resonant ICD (RICD) where the precursor excitation to form an inner-shell vacancy is accomplished by promoting an inner electron to an excited state by an external stimulant, generally electromagnetic radiation [17,18] or, more recently, chargeparticle impact [21]. A theoretical study of RICD followed by Ne 2s → np excitations in MgNe clusters suggested the leading contribution of RICD among other interatomic decay modes [22].…”
mentioning
confidence: 99%
“…It can be induced by photoionization (see e.g. [2,3]), photoexcitation [9][10][11][12], Auger decay [13,14], ion impact [15][16][17], and electron impact [18] or as in the present case after shakeup [19]. The most extreme system for which ICD has been reported is the Helium dimer [20,21].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…This is, however, not the only reaction pathway through which two ions can be created [11,[23][24][25][26]. According to the nomenclature used in [23] the sequential ionization discussed so far is referred to as CE.…”
Section: Fragmentation Mechanismsmentioning
confidence: 99%